Clerical Cluster Technical Terms. English-Thai Lexicon. Introduction to Clerical Cluster. Thai Version. Multi-Cultural Competency-Based Vocational Technical Curricula Series - Shin, Masako T.; Southern Illinois Univ., Carbondale. School of Technical Careers ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This English-Thai lexicon and program introduction for the clerical cluster is one of eight documents in the Multicultural Competency-Based Vocational/Technical Curricula Series. It is intended for use in postsecondary, adult, and preservice teacher and administrator education. The first two sections provide Thai equivalencies of English clerical cluster technical terms and Thai equivalencies of English clerical cluster equipment and tools. Section 3 is the Thai version of "Introduction to Clerical Cluster." The duty-task index is then provided in Thai with major headings also given in English. (YLB)
Sponsoring Agency: Illinois State Board of Education, Springfield. Dept. of Adult, Vocational and Technical Education.
Contract Number: R-33-32-J-0542-400.
ERIC Note: For related documents see ED 205 781-788 and CE 034 378-385. Translated by Pradit Chatcharhtkoon.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accounting; Administrator Education; Adult Vocational Education; Bilingual Education; Bilingual Instructional Materials; Clerical Occupations; Competency Based Education; Glossaries; Limited English Speaking; Mathematics; Office Occupations Education; Postsecondary Education; Preservice Teacher Education; Thai; Typewriting; Vocabulary; Reference Materials, Vocabularies/Classifications.; Guides, Classroom -- Learner; Multilingual/Bilingual Materials